Modelo Arquitectónico para la Estructura Computacional de la Universidad Distrital Virtual - Pérez Castillo, José Nelson (Ingeniería, 2000)
Although primary missions of the university (the creation, preservation, integration, transmission, and application of knowledge) are not changing, the particular realization de each of these roles is changing dramatically.Communication, computing,networking and knowledge engineering and management technologies expand the reach and range de traditional universities and enable students to synthesize on-campus with online experiences. This paper discuss an architectural model for the computational structure of the future Virtual Distrital University and outlines key technologies to guide the implementation of this academic model.